A Retrospective Study of Incidence and Predictors on Mother-to-Child Transmission of HIV among HIV-Exposed Infants in West Guji Zone, Southern Ethiopia - Girish Degavi; Boko Loka Safayi; Shiferaw Gelchu Adola; Biniyam Demisse; Takala Utura; Udessa Gemeda; Sarah Ezhil Kelna Edwin; Fitsum Demissie (AIDS Research and Treatment)
Background. The transmission of HIV from mother to child among HIV-positive infants is estimated to be higher than 20%, despite the fact that antiretroviral treatment is available for antenatal mothers with HIV. In Ethiopia, the prevalence of HIV transmission from mother to child among infants aged one and a half years is estimated to be approximately 15.7 percent. Methods. A retrospective cohort analysis using a simple random sampling technique was incorporated among 422 HIV-exposed babies and their mothers who were randomly chosen and screened using OPD (outpatient card) from March 2019 to March 2021 in the general hospitals of West Guji zone, Oromia, Ethiopia. The data were coded and entered into EpiData version 4.6.1 and exported to SPSS version 23 for cleaning and analysis. Result. The study revealed that at the end of follow-up, 3.8% of the HIV-exposed infants were found to be HIV positive. Poor adherence of infant for CPT (AOR: 5.6; 95% CI: 1.010–27.24), father not enrolled to ART (AOR: 4.4; 95% CI: 1.187–15.724), age of infants at enrollment >6 weeks (AOR: 4.5; 95% CI: 1.102–16.1), mother’s enrollment to PMTCT during labor and delivery or after (AOR: 6.84; 95% CI: 1.316–42.743), and mothers on the WHO clinical stage mild or advanced (AOR: 3.6; 95% CI: 1.146–16.842) was found to be the most important significant predictors of mother-to-child transmission of HIV. Conclusion. Several factors included in the study were the main predictors of mother-to-child transmission of HIV. The study concluded that there are some lacunae in the prevention of MTCT of HIV but that the incidence of MTCT of HIV was significantly lower in this part of the world.